Influence of spatial frequency in visual stimuli for cVEP-based BCIs: evaluation of performance and user experience - Fernández-Rodríguez, Álvaro; Martínez-Cagigal, Víctor; Santamaría-Vázquez, Eduardo; Ron-Angevin, Ricardo; Hornero, Roberto (Frontiers in Human Neuroscience, 2023)
Code-modulated visual evoked potentials (c-VEPs) are an innovative control signal utilized in brain-computer interfaces (BCIs) with promising performance. Prior studies on steady-state visual evoked potentials (SSVEPs) have indicated that the spatial frequency of checkerboardlike stimuli influences both performance and user experience. Spatial frequency refers to the dimensions of the individual squares comprising the visual stimulus, quantified in cycles (i.e., number of black-white squares pairs) per degree of visual angle. However, the specific effects of this parameter on c-VEP-based BCIs remain unexplored. Therefore, the objective of this study is to investigate the role of spatial frequency of checkerboard-like visual stimuli in a c-VEP-based BCI. Sixteen participants evaluated selection matrices with eight spatial frequencies: C001 (0 c/ • , 1×1 squares), C002 (0.15 c/ • , 2×2 squares), C004 (0.3 c/ • , 4×4 squares), C008 (0.6 c/ • , 8×8 squares), C016 (1.2 c/ • , 16×16 squares), C032 (2.4 c/ • , 32×32 squares), C064 (4.79 c/ • , 64×64 squares), and C128 (9.58 c/ • , 128×128 squares). These conditions were tested in an online spelling task, which consisted of 18 trials each conducted on a 3×3 command interface. In addition to accuracy and information transfer rate (ITR), subjective measures regarding comfort, ocular irritation, and satisfaction were collected. Significant differences in performance and comfort were observed based on different stimulus spatial frequencies. Although all conditions achieved mean accuracy over 95% after 2.1 s of trial duration, C016 stood out in terms user experience. The proposed condition not only achieved a mean accuracy of 96.53% and 164.54 bits/min with a trial duration of 1.05 s, but also was reported to be significantly more comfortable than the traditional C001 stimulus. Since both features are key for BCI development, higher spatial frequencies than the classical black-to-white stimulus might be more adequate for c-VEP systems.Hence, we assert that the spatial frequency should be carefully considered in the development of future applications for c-VEP-based BCIs.